Die Freimaurer im Alten Preußen 1738-1806, Die Logen in Pommern, Preußen Die Logen in Pommern, Preußen und Schlesien - Gerlach, Karlheinz (Studien Verlag, 2009)
The research "The Freemasons in Ancient Prussia 1738 - 1806" is the result of a research project of the Research Centre for Democratic Movements at the Faculty of Humanities of the University of Innsbruck in cooperation with the Scientific Commission for the Research of Freemansory, headed by Prof. Dr. Helmut and financed by the Fund for the promotion of scientific research (FWF) in Vienna.The main sources for this research were in the Masonic papers and documents of the ancient Prussian lodges, preserved at the Geheimes Staatsarchiv Preußischer Kulturbesitz, Berlin-Dahlem, the sources of the Austrian State Archive, Department Haus-, Hof- und Staatsarchiv, Vienna, a series of other archives and libraries, the Masonic literature as well as the relevant literature on regional, social and biographical history.The reference book includes the period 1741 - 1806 in eastern Brandenburg-Prussia within the boundaries before the Second division of Poland in 1793, i.e. Pomeriana (excluding Swedish Pomerania), the Kingdom of Prussia (East Prussia), Silesia conquered by Prussia in 1740/41, and West Prussia, which was annected to Prussia after the First division of Poland in 1772. Pomerania and Silesia were parts of of the Holy Roman Empire, whereas East and West Prussia were situated beyond its boundaries.The Masonic lodges have been analyzed according to analoque criteria: their development in historical and regional context, their membership and social structure, societal, social and cultural activities as well as their influential role in civic society. For the first time, Masonic and biographically commented lists cover the entire membership of the analyzed region. Thus the book is also a contribution to a prosopographical and family history. The Masonic lodges were a specific form of a associations of the 17th and 18th centuries with a similar organizational structure, but on a broader social basis. They followed a system of successive steps (grades) with an ethical and moral programme of forming the human character with the aim of the introduction into a so-called Masonic secret. Since 1740 the apolitical lodges, bringing together different confessions, were associations legitimated by the Prussian state, which could freely develop without intervention by the police. The "Common Law of the Prussian States" defined them as closed societies.Within the analyzed period 56 lodges (four field lodges included) constituated themeselves in 31 towns and on five landed properties of noble Masonic members. They organized 5,375 members, the 61 members of the field lodges and the 350 Serving Brothers included, i.e. more than one third of all registered freemansons in Brandenburg-Prussia. Increasingly the freemasons were members of the social strata and groups, connected with the advancement of the Prussian state: they were members of the nobility and citizens, servants of the administration, theologians and teachers, who had been educated at enlightened universities, officers who engaged spiritually and socially, manufacturers and bankers, printers and booksellers, doctors and chemists, and artists. Members of the substrata were accepted only as Serving Brothers, and women were not acknowledged as members of the lodges at all. Although the provinces Pomerania, Prussia and Silesia had common features in general, they showed significant differences, nevertheless.In Pommerania until 1806 15 lodges were founded in eight cities. With the exeption of Stettin, a centre of trade and craft with a garrrison, as well as Stargard, the social basis was thin, that is why the lodges were unstable. About 960 freemasons have been registered in West and Middle Pomerania, mainly noble officers and civil servants, and 81 Serving Brothers. Only Stettin had a broader social basis. In East Prussia twelve lodges were founded in six towns and at one landed property of a noble member. About 1,465 freemasons have been registered as well as 86 Serving Brother